Government House, Trinidad - (:unkn) unknown (Algernon E. Aspinall, 2009)
A front view of the main building of Government House with a variety of tropical plants of the Botanical Gardens and at the background is the St. Ann's hills. The postcard is addressed to Mr. H. Foyle, Northampton, England. The postcard is dated October 4th, 1906.
Colour: Coloured; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Public buildings--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Botanical gardens--Trinidad and Tobago; 1906; President's House, The